2022
DOI: 10.1007/s12070-021-03052-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Management of Tongue Involvement in COVID-19 Patients

Abstract: Evaluate the lingual manifestations of COVID-19, and provide a clinical guide in managing these symptoms. Electronic databases, such as PubMed/Medline, and Scopus were searched until November 1, 2020, and only randomized controlled trials, cross-sectional and cohort studies, as well as case reports and series, and review articles in English were considered. A total of 40 studies were included in this study. Lingual involvement has been extensively reported in patients with coronavirus disease 2019 (COVID-19). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, it is unknown if oral mucosal lesions in patients are driven on by a direct infection with SARS-CoV-2 ( Erbaş et al, 2022 ). The causes of oral mucosal lesions may also be related to oral cavity local immune responses, fungus infections, drug side effects, injuries caused by medical devices, vasculitis, microcirculation issues, etc ( Viner and Whittaker, 2020 ; Amorim dos Santos et al, 2021b ; La Rosa et al, 2021 ; Orilisi et al, 2021 ; Mohseni Afshar et al, 2022 ). Cell vacuolization, inflammatory cell infiltration, thrombosis, hemorrhage, necrosis, and other pathological abnormalities of the oral mucosa in COVID-19 individuals are additional oral mucosal abnormalities ( Silveira et al, 2022 ).…”
Section: The Mechanisms Of Oral Manifestationsmentioning
confidence: 99%
“…However, it is unknown if oral mucosal lesions in patients are driven on by a direct infection with SARS-CoV-2 ( Erbaş et al, 2022 ). The causes of oral mucosal lesions may also be related to oral cavity local immune responses, fungus infections, drug side effects, injuries caused by medical devices, vasculitis, microcirculation issues, etc ( Viner and Whittaker, 2020 ; Amorim dos Santos et al, 2021b ; La Rosa et al, 2021 ; Orilisi et al, 2021 ; Mohseni Afshar et al, 2022 ). Cell vacuolization, inflammatory cell infiltration, thrombosis, hemorrhage, necrosis, and other pathological abnormalities of the oral mucosa in COVID-19 individuals are additional oral mucosal abnormalities ( Silveira et al, 2022 ).…”
Section: The Mechanisms Of Oral Manifestationsmentioning
confidence: 99%
“…The pathophysiological mechanisms are not yet fully understood [ 20 ]. However, in the case of SARS-CoV-2 infection, taste impairment is linked to olfactory dysfunction or neurological damage [ 21 ]. Although weariness, headaches, arthralgia, myalgia, and fever are among vaccinations’ most frequent side effects, olfactory or gustatory impairment has not been mentioned in research [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are edentulous or who have HIV, advanced cancer, graft-vs-host disease, trigeminal neuralgia, amyotrophic lateral sclerosis, or chronic xerostomia, or who have received recent radiation therapy to the head or neck, are at increased risk of black hairy tongue . Black hairy tongue has also been reported in patients with COVID-19 …”
Section: Discussionmentioning
confidence: 99%
“…1,2,4 Black hairy tongue has also been reported in patients with COVID-19. 6 Although the exact prevalence of black hairy tongue is unknown and varies among populations, studies of dental and oral medicine outpatients have reported a prevalence of 1.2% to 11.3%. 4,[7][8][9] Black hairy tongue is 3 times more common in males than females, which may be due to higher rates of cigarette smoking and poor oral hygiene among men.…”
mentioning
confidence: 99%